Effects of salicylic acid for alleviating biological activities in sorghum against tannery wastewater (Bangladesh Journal of Botany, 2026)
This study evaluated the protective effects of salicylic acid (SA) on Sorghum bicolor L. exposed to tannery wastewater containing heavy metals Cr, Pb, and Cd. Treatments included 30, 50, 70, and 100% tannery wastewater, 100 to 200 mg/l salicylic acid, and their combinations. Tannery wastewater (TWW)  reduced root and shoot length, biomass, photosynthetic rate, and relative water content while increasing oxidative stress biomarkers such as malondialdehyde (MDA). Antioxidant enzymes (SOD, POD, CAT, NR, GR, and GPX) showed an initial increase under moderate tannery wastewater stress, followed by inhibition at higher levels. Application of 200 mg/l SA markedly improved growth by 30-41%, restored chlorophyll and carotenoids by 29-38%, and enhanced enzymatic antioxidants.Bangladesh J. Bot. 55(2): 403-410, 2026 (June)